Biogas Quality Across Small-Scale Biogas Plants (International Journal of Innovative Research in Computer Science & Technology, 2021)
Fermentation-based bioenergy  production is gaining popularity owing to its ease of use  and broad range of feedstock options. Anaerobic  fermentation of biological waste resources is widely  regarded as a cost-effective and well-proven technique  that allows for waste management and energy generation  at the same time. In the developing world, The use of  small-scale biogas plants to change waste into gas by  aerobic digestion of organic materials is becoming more  common. Biogas produced in small-scale biogas systems  is of poor grade, was assessed in this study since it has a  direct impact on its usage (as a fuel for biogas cookers)  and may affect the choice to purchase such equipment. At  107 small-scale biogas facilities, the composition of  biogas was tested using a multifunctional portable gas  analyser. A questionnaire survey of biogas plant owners  (n = 107) was used to gather additional data at the home  level. The average daily biogas output is 0.499 m3, which  is insufficient to meet the needs of rural families that rely  on other sources of energy. In terms of biogas  arrangement, biogas plants earlier than five years had a  mean content of 65.44 percent methane (CH4) and 29.31  percent carbon dioxide (CO2), whereas biogas plants  elder than 5 years had a mean content of 64.57 percent  CH4 and 29.93 percent CO2.
Keywords: Biogas; CO2; Energy; Environment; Technology